MOBILE VOTING PEMILIHAN SENAT MAHASISWA STMIK SUMEDANG - Fathoni Mahardika (Sekolah Tinggi Ilmu Administrasi Sebelas April Sumedang, 2016)
Election is a way to realize the principle of democracy is normally done by choosing to use media and supplied ballot polling stations (TPS). STMIK Sumedang has also been applied to the electoral system for the election of Chairman of the Senate but there are problems faced by the committee in STMIK Sumedang because Many students or prospective voters who can not convey the right to vote, because the implementation time and lecture schedules run concurrently. The method used to create mobile voting Student Senate Election uses prototype method. Stages in the first of these methods is the identification of problems and needs and then to design prototype system and evaluating whether the system has been built as expected. With the Mobile Student Senate Election Voting can help the student union election process STMIK Sumedang good for the voters or the student and the committee (KPUM) that the management of the results of the voting can be managed properly.